Analysis of the Effect of Providing MNBs Organic Liquid Fertilizer on the Growth of Pueraria Javanica Plants in Coal Mining Areas - Yasmi Antara; Abdul Razak; Iswandi Umar; Mulya Gusman; Nur Efendi (Postgraduate, University of Mataram, 2023)
Apart from ex-mining land which requires management and rehabilitation using soil microbial communities, reclamation activities require time and technology with high costs and results that are not necessarily effective and efficient. One effective way is to provide organic fertilizer which contains lots of microbes and is able to neutralize soil acidity. This type of research is experimental research with a research design using a Completely Randomized Design (CRD) 4 x 6. The population of this research is all Ruji Nut Plants (Pueraria Javanica) that grow in the PT Mine Wire House area. The main natural coal sampled in this research were 24 Ruji Nut Plants (Pueraria Javanica). The results of this research were that administering NPK solution and Micro Nano Bubbles (MNBs) was proven to help accelerate stem growth, number of leaves, number of leaf branches, root length and increase the biomass of Ruji Nut (Pueraria Javanica) plants in planting media with minimal topsoil. The dosage of Organic NPK Solution and Micro Nano Bubbles (MNBs) for optimal growth of Pueraria javanica plants was in treatment 4 (90 ml), where in treatment 4 the average stem growth, number of leaves, number of leaf branches, root length and plant biomass reached optimal point. So the use of Organic NPK solution using Micro Nano-Bubbles (MNBs) is more effective and environmentally friendly because it is formed from organic materials.